PERSEPSI MAHASISWA ILMU KOMUNIKASI UNTAG SURABAYA TENTANG ACARA â€œMANCING MANIAâ€ DI TRANS 7 (STUDI DESKRIPTIF PERSEPSI MAHASISWA ILMU KOMUNIKASI FISIP UNIVERSITAS 17 AGUSTUS 1945 SURABAYA ANGKATAN 2013-2016 ) - Putro, Widiyatmo Eko (Universitas 17 Agustus 1945 Surabaya, 2017)
Among the programs shown by television stations, sporting events is a program that manyshown by private television stations. Fishing Mania one of them, an exercise program that aired onTrans 7. Fishing Mania is the only program in Indonesia which tells the good fishing activities at seaand in rivers. The activities of writer wanted to know how students' perceptions of SocialCommunication Sciences University August 17, 1945 Surabaya on Fishing Mania events in Trans 7.With the aim to describe the perception of students of Social Communication Sciences UniversityAugust 17, 1945 Surabaya on impressions and the credibility of the presenter after watching FishingMania Trans 7. This is a descriptive study with a quantitative approach, where researchers collectedprimary data that is distributing questionnaires to 40 respondents. The object of research is thestudents of Social Communication Sciences University August 17 1945 Surabaya force from 2013 to2016 who has ever watched the show Fishing Mania. From the results obtained in this study, 76% ofrespondents expressed positive about Fishing Mania. Fishing Mania respondents considered the showcan be entertaining and provide knowledge about the profession or the world of broadcasting TVBroadcasting.Keywords: Perception, Professional Broadcasters, Mass Communication.